Efforts to harmonise and promote a stone fruit certification scheme in the Mediterranean countries - Di Terlizzi B.; Caglayan K.; Gavriel I.; Myrta A. (Stone fruit viruses and certification in the Mediterranean countries: problems and prospects, 1998)
The awareness of potentiality disastrous consequences to stone fruit crops from virus diseases (i.e. Sharka) had alarmed the scientific community and prompted the initiation of national and international projects for the production of virus-free stocks through certification programmes. To promote a clean stock programme in the Mediterranean region, the Centre International de Hautes Etudes Agronomiques Méditerranéennes (CIHEAM) has promoted the 'Mediterranean Network for Virus Disease Assessment and Sanitation of Stone Fruit Trees' (MNFT). Various proposal have been discussed to improve and harmonise current certification schemes starting from EPPO stone fruit protocols now in operation in different countries. Other proposal for more reliable techniques for disease detection used in these programmes were included.